Receptive and productive vocabulary acquisition: effectiveness of three types of tasks. Results from French students of Spanish as second language - San Mateo-Valdehíta, Alicia; Criado de Diego, Cecilia (Onomázein, 2021)
This study presents the results of research on the vocabulary acquisition of French students of Spanish as second language. The aim is to know (1) which of these three vocabulary-learning tasks is more effective: definition-choosing, gap-filling or sentence-writing; and (2) which kind of knowledge, receptive or productive, the participants acquire with each vocabulary-learning task. The analysis shows that the most effective task is sentence-writing, then gap-filling and, in the third place, definition-choosing. Also all the three learning tasks trained students to complete above all activities which require a receptive knowledge of the words—definition-choosing and gap-filling tasks—, but they were much less prepared to carry out the sentence-writing task, which requires a productive knowledge of the words. The only productive task proposed—sentence-writing—is the one that allowed the students to learn receptively and productively a higher number of words. We associate our results with the Involvement Load Hypothesis and Technique Feature Analysis.